Pynchon and Philosophy Wittgenstein, Foucault and Adorno - Eve, Martin Paul (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Pynchon and Philosophy radically reworks our readings of Thomas Pynchon alongside the theoretical perspectives of Wittgenstein, Foucault and Adorno. Rigorous yet readable, Pynchon and Philosophy seeks to recover philosophical readings of Pynchon that work harmoniously, rather than antagonistically, resulting in a wholly fresh approach. Dr. Martin Paul Eve is a lecturer in literature at the University of Lincoln, UK. In addition to editing the open access journal of Pynchon Studies, Orbit, he has work published or forthcoming in Textual Practise, Neo-Victorian Studies, C21, Pynchon Notes and several edited collections. This book was originally published with exclusive rights reserved by the Publisher in (2014) and was licensed as an open access publication in [SEPTEMBER 2021] under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/), which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license if changes were made. This is an open access book.